Improving the aerobic and anaerobic capacity of kickboxers through polarised training - Gerasimov, M.V.; Mironov, A.O. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the effectiveness of polarised training for kickboxers during the preparatory period, based on the integrated development of the athletes’ aerobic and anaerobic capacities. Methods and structure of the study. During the preparatory period, prolonged low-intensity exercise was combined with the execution of techniques at high speed. Following five training sessions aimed at developing general endurance, speed-strength training was conducted to maximise the speed and power of punches and kicks. The following parameters were measured: maximum and anaerobic power; power decline index; and maximum oxygen consumption (MOC). Results and conclusions. Polarised training improves kickboxers’ anaerobic capacity to a greater extent, whilst aerobic energy supply mechanisms improve to a lesser extent. When planning further training, greater attention should be paid to developing kickboxers’ aerobic capacity.